Letter (copy) : Ray Cox Memorial - Tewson, Vincent
041-0045-001 HVT/EK/630. Secretary's. 3rd April, 1937. Mr. L. Witt, The Joint Council of the Southampton Trades Council, Labour Party and Co-operative Society, Prospect House, 160, Above Bar, SOUTHAMPTON. Dear Mr. Witt, RAY COX MEMORIAL. Further to my letter of yesterday, I am going further into the matter of the anaesthetic apparatus. Dr. Morgan has made some preliminary enquiries in regard to price and two estimates will be in our possession early next week. It now appears that a British apparatus is vastly superior to those produced in France and it does appear from more than one point of view that it would be advisable to buy in this country. I am just adding this information to my letter of yesterday's date in order to clarify the position. Perhaps you would let me have your comments on the points I raised yesterday. Yours sincerely, Assistant Secretary. 292/946/41/45